BOOK REVIEW: TEACHING WORLD LANGUAGES WITH THE FIVE SENSES, PRACTICAL STRATEGIES AND IDEAS FOR HANDS-ON LEARNING - Suja, Aidillah; Muassomah, Muassomah; Sutaman, Sutaman (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This book review discusses Elizabeth's journey as a mother and teacher who combined her personal and professional experiences to design a language teaching method that engages the five senses. The book “Teaching World Languages with the Five Senses, Practical Strategies and Ideas for Hands-On Learning” that resulted from her research provides deep insights into language acquisition in the brain. Each book’s 11 chapters address various topics, from language learning in the brain to five-sense teaching methods to cultural responsiveness in the 21st-century language classroom and decolonizing the world language curriculum. Emphasis is placed on teachers adapting to student diversity, dealing with learning anxiety, and providing approaches that support higher-order thinking skills. Suitable for all language teachers worldwide, this book presents an innovative approach involving the five senses in language learning, emphasizing a basic understanding of the brain as a foundation for more effective teaching practices.